Late Neoliberalism and its Discontents in the Economic Crisis - Della Porta, Donatella. author. aut Link
XV, 307 p. 19 illus., 2 illus. in color.
Keywords: This book analyses protests against the Great Recession in the European periphery. While social movements have long been considered as children of affluent times - or at least of times of opening opportunities - these protests defy such expectations, developing instead in moments of diminishing opportunities in both the economic and the political realms. Can social movement studies still be useful to understanding these movements of troubled times? The authors offer a positive answer to this question, although specify the need to bridge contentious politics with other fields, including political economy. They highlight differences in the social movements’ strength and breadth and attempt to understand them in terms of three sets of dimensions: a) the specific characteristics of the socio-economic crisis and its consequences in terms of mobilization potential; b) the political reactions to it, in what we can define as political opportunities and threats; and c) the social movement cultures and structures that characterize each country. The book discusses these topics through a contextualized analysis of anti-austerity protest in the European periphery.